Heart-type Fatty Acid-binding Protein (H-FABP) sebagai Diagnostik Awal dan Prognostik Infark Miokard Akut - Ni Made Utami Wulandari; Putu Wika Pramesti Iswari; Yusra Pintaningrum (Faculty of Medicine, Universitas Mataram, 2023)
Acute myocardial infarction (AMI) remains one of the leading causes of mortality and morbidity worldwide. Early diagnosis and accurate prognosis are vital to improve patient outcomes. Heart-type Fatty Acid-binding Protein (H-FABP) has emerged as a potential biomarker for AMI. H-FABP is a cytoplasmic protein encoded by the FABP3 gene, situated on chromosome 1 in the human genome. It plays a crucial role in active fatty acid metabolism and is implicated in the absorption, cellular metabolism, and/or transport of polyunsaturated fatty acids (PUFAs). During the pathogenesis of acute coronary syndrome (ACS), H-FABP is rapidly released into the circulation when myocardial ischemic injury occurs. Its early detection, around 1-2 hours after AMI, with a peak at 5-10 hours, and normalization within 24-36 hours, makes H-FABP an ideal candidate for early diagnostic and prognostic evaluation in AMI patients. Despite its excellent prognostic value, H-FABP's diagnostic sensitivity outweighs its specificity for AMI. This review discusses the potential of H-FABP as an early diagnostic and prognostic marker for AMI and emphasizes further studies and research are needed regarding the use of H-FABP as a diagnostic and/or prognostic marker for AMI.